Airborne Microplastics from Waste as a Transmission Vector for COVID-19 - Qingyang Liu; James Schauer (Aerosol and Air Quality Research)
Abstract Occurrences of microplastics (plastic particle < 5 mm) have been observed in various environmental media (e.g., soil, water and air) worldwide, posing a threat to ecological, human, and animal health. Microplastics could also serve as vectors which transport toxic hydrophobic organic compounds around the globe and negatively affect the environmental quality. This paper analyzes the possible link between airborne microplastics from waste that are contaminated with SARS-CoV-2, and the transmission of SARS-CoV-2. In addition, measures for controlling the transmission of SARS-CoV-2 in airborne microplastics were discussed. Our study indicates that precautionary action regarding the management of contaminated plastic waste should be considered in order to combat the spread of SARS-CoV-2 through airborne microplastic.